An investigation of healthcare communication with patients with disability: The case of medical practitioners - Moussa, Yasser; Alzahrani, Fahad; Elshemy, Radwa; Fawzy, Shereen (Edelweiss Applied Science and Technology, 2025)
In today’s healthcare landscape, effective communication is essential for delivering patient-centered care, especially to individuals with disabilities. Despite existing efforts, many gaps remain in physician-patient communication, underscoring the need for alternative solutions such as remote or in-person sign language interpreters and inclusive training programs. This study seeks to understand healthcare providers’ perspectives and experiences in communicating with patients with disabilities. Adopting a mixed-methods approach, the research includes survey responses from medical practitioners, observation of clinical interactions, and thematic analysis of six unstructured interviews. By highlighting the perspectives of practitioners across specialties, the study contributes to addressing structural gaps in policy and practice. Its recommendations are positioned to support national health strategies focused on equitable access and professional development. The findings aim to inform the development of targeted interventions that promote inclusive and effective communication in clinical settings. For instance, technology-based platforms such as LiveCare, which offer real-time access to sign language interpreters and other accessibility tools, demonstrate the potential of scalable solutions to bridge these gaps and enhance patient-provider interactions.